Program Pembelajaran Bahasa Arab Berbasis Kearifan Lokal untuk Menumbuhkan Minat Budaya dan Bahasa bagi Remaja - Zain, Biqi (Himpunan Mahasiswa Program Studi (HMPS) Pendidikan Bahasa Arab Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Jember, 2026)
This study aims to assess the effectiveness of local wisdom-based Arabic language learning in increasing learning interest, language proficiency, and cultural awareness among adolescents in Kembang Village, Pacitan. The program integrates local cultural elements, folklore, proverbs, traditional rituals, and traditions into Arabic language learning activities. The method used was classroom action research with qualitative and quantitative approaches, through observation, interviews, language proficiency tests, and documentation of participant activities. The results showed a significant increase in learning interest, language competency (vocabulary, grammar, speaking, and listening), as well as active participation, creativity, and collaboration among participants. The program also encouraged the formation of cultural identity, increased appreciation of local values, and viewed language proficiency as a means of cultural preservation. These findings confirm that local wisdom-based Arabic language learning is effective in strengthening both language skills and cultural awareness. The research recommendation is to expand the implementation of this model and provide teacher training for creative language and cultural integration so that the program is sustainable and has a broader impact on the younger generation.